Correlation Between Intracranial Carotid Artery Calcification and Prognosis of Acute Ischemic Stroke After Intravenous Thrombolysis - Shen, Yuan; Dong, Zhifeng; Xu, Gang; Zhong, Jianguo; Pan, Pinglei; Chen, Zhipeng; Shi, Haicun (Frontiers in Neurology, 2022)
Objective: To investigate the correlation between prognosis and intracranial carotid artery calcification (ICAC) in patients with acute ischemic stroke (AIS) who receive intravenous thrombolysis (IVT). Methods: A total of 156 AIS patients who received IVT from March 2019 to March 2020 were enrolled. The modified Woodcock visual score was used to evaluate ICAC in nonenhanced head CT scans. Patients were divided into high calcification burden (HCB; score≥3) and low calcification burden (LCB; score < 3) groups. Demographic, laboratory, imaging and clinical data were compared between the two groups, and whether HCB was a prognostic factor was evaluated. Results: Compared with the LCB group, the HCB group had a higher incidence of atrial fibrillation (49.2% vs 22.1%, P < 0.001) and coronary heart disease (24.6% vs 10.0%, P = 0.019) and higher serum homocysteine (15.31 [12.15,17.50] vs 14.40 [11.20, 16.20], P = 0.036) and hemoglobin A1c (6.93±1.77 vs 6.37±0.74, P=0.023) levels. Binary logistic regression analysis showed that atrial fibrillation (OR = 3.142, 95% CI: 1.465-6.739, P = 0.003) and HbA1c (OR = 1.496, 95% CI: 1.057-2.117, P = 0.023) were independent risk factors for ICAC. After adjusting for other risk factors, symptomatic-side and bilateral ICACs were independent risk factors for poor prognosis (OR=1.969, 95% CI: 1.220-3.178, P=0.006) and mortality (OR=4.245, 95% CI: 1.114-16.171, P=0.034) in patients with AIS who received IVT. Conclusion: ICAC is closely related to the prognosis of acute ischemic stroke after intravenous thrombolysis.